1997
DOI: 10.1149/1.1837388
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Various Fe‐Based Precursors on Carbon Black and Graphite Supports to Obtain Catalysts for the Reduction of Oxygen in Fuel Cells

Abstract: Three synthetic paths have been used to prepare iron-based catalysts for the electrochemical reduction of oxygen in solid polymer fuel cells. The catalyst precursor used in the first synthetic path was a dispersion of Fe(OH)2 on carbon black (Vulcan) that was reduced at 600°C in H2. The second synthetic path involved a method to intercalate FeC13 that was first used with graphite and then extended to Vulcan. The oxidized iron was reduced by either heating the resulting materials at 600°C in 112 or by reacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 3 publications
1
43
0
Order By: Relevance
“…Van Veen et al were one of the earlier groups to report the formation of a new catalytic site upon high temperature treatments of carbon-supported organo-metallic macrocycles [8]. Later studies have reported that it was not necessary to begin with organic macrocycles in order to produce active and stable nonnoble metal ORR electrocatalysts [9]. Often heating an N and C source over metal particles was sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Van Veen et al were one of the earlier groups to report the formation of a new catalytic site upon high temperature treatments of carbon-supported organo-metallic macrocycles [8]. Later studies have reported that it was not necessary to begin with organic macrocycles in order to produce active and stable nonnoble metal ORR electrocatalysts [9]. Often heating an N and C source over metal particles was sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding both the catalytic activity and stability of pyrolyzed M-N/C catalysts, there is a general agreement in the literature that four factors are necessary in achieving an active and stable non-Pt metal ORR catalyst: transition metal, nitrogen coordinators on these catalysts, source carbon support and pyrolysis [15]. As established by Dodelet and co-workers [15][16][17] and now widely confirmed by experiments, nitrogen is a necessary component of the catalyst site in order to form an active catalyst. This is why several different types of nitrogen-containing compounds have been employed as the precusors to form M-N/C complexes.…”
Section: Introductionmentioning
confidence: 92%
“…11 Table 1 summarized the preparation parameters and the corresponding ORR activities of NNMCs reported in the past two years. [14][15][16][17][18][19][20][21][22][23][24][25][26] Also, nitrogen is a necessary component of the catalyst site to form an active catalyst as es-tablished by Fournier et al 27 and widely confirmed by experiments. Hence, we only collect the literatures regarding the addition of nitrogen-containing precursor to the synthetic reactions during preparation.…”
Section: Non-noble Metal-based Electrocatalysts Historymentioning
confidence: 99%